ENGARUH LAMA PUTARAN MESIN PENGADUK BETON TERHADAP KUAT TEKAN BETON f’c 14.5 Mpa - Sichab Rabbani; Rasio Hepiyanto (Universitas Islam Lamongan, 2017)
Based on the various properties of concrete, it is necessary to investigate the effect of mixing time of concrete mixture on the compressive strength of concrete. The length of stirring of the concrete mixture in question is the amount of time spent mixing the concrete in minutes. The experiment was performed using a concrete mixing machine with stirring times of 5, 10, 15, 20, 25, and 30 minutes. The method of data analysis begins with the investigation of cement, coarse and fine aggregates. The experiment was conducted at the laboratory of Lamongan Islamic University, using molen machine for mixing concrete and test specimens in test with concrete compressive strength test. From concrete compressive strength test, concrete compressive strength with rotation time for 5, 10, 15, 20, 25 and 30 minutes were 15,366 MPa, 17,021 MPa, 15,839 MPa, 15,603 MPa, 16,076 MPa, 15,603Mpa at age 28 days. Based on the test, the highest compressive strength of concrete was obtained on stirring for 10 minutes with a compressive strength of 17,021 Mpa or 16.872% of normal concrete.